2007
DOI: 10.1111/j.1745-7254.2007.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 acts as a molecular chaperone in late-phase activation of extracellular signal-regulated kinase 1/2 stimulated by oxidative stress in vascular smooth muscle cells

Abstract: Aim: To investigate whether cytosolic heat shock protein 90 (HSP90) acts as a molecular chaperone on the activated extracellular signal-regulated kinase 1/2 (ERK1/2) and cell proliferation stimulated by reactive oxygen species (ROS) in rat vascular smooth muscle cells (VSMC). Methods: VSMC were exposed to 1 µmol/L LY83583 (6-anilinoquinoline-5,8-quinolinedione, producer of ROS) for 120 min in the presence or absence of 5 µmol/L geldanamycin, a specific inhibitor of HSP90. Then the total, soluble, and insoluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…HSP90 binding to its client protein may protect against physiological oxidative stress [39], [40]. Here, our data demonstrated that CHX specifically decreased HSP90 protein expression (Fig.…”
Section: Resultssupporting
confidence: 63%
“…HSP90 binding to its client protein may protect against physiological oxidative stress [39], [40]. Here, our data demonstrated that CHX specifically decreased HSP90 protein expression (Fig.…”
Section: Resultssupporting
confidence: 63%
“…ROI caused oxidative stress and contributes to various cancer processes, including migration and invasion (McCord, 2002;Jung et al, 2006). Oxidative stress-induced stimulation of HSP90 was also reported (Liu et al, 2007). Therefore, we hypothesized that reduced ROI by Erdr1 leads to suppression of HSP.…”
Section: Discussionmentioning
confidence: 87%
“…Evidence suggests that HSP, especially HSP70, are involved in the development of thermotolerance in broilers (18,19) and in human and mouse cells (33)(34)(35) . In the present study, the up-regulations of both HSP70 mRNA and protein in the heart, liver and breast muscle of broiler breeders exposed to HT might favour an anti-heat stress response.…”
Section: R E T R a C T E Dmentioning
confidence: 99%